A dimensão espiritual da escultura através da obra de XIX artistas - Serrano, Carolina, 1994- (2018)
The spiritual dimention in art, in the European context, has been, for centuries, almost exclusively related with religion. However, in the modernity, with the loss of prominence of religion, and with the divorce of art and the Church, that dimention has became accessible to be freely and autonomously explored by art, and in this specific case, by sculpture. If, in general, from the point of view of modernism, it is known that art has lost its notion of transcendence, in accordance with a destructive demand of the artistic tradition, concentrating, instead, on exploiring and evaluating its own possibilities, however, it is also possible to notice the presence of a strong spiritual dimension in the life and work of many modern and contemporary artists. This dissertation is the result of a research of this spiritual dimention in the 20th and 21st century sculpture, through an analysis of the life, work and/or cultural circumstances of nineteen artists, namely Constantin Brancusi (1876-1957), Marcel Duchamp (1887-1968), Jean Arp (1886-1966), Jacob Epstein (1880-1959), Alberto Giacometti (1901-1966), Henry Moore (1898-1986), Barbara Hepworth (1913-1975), Isamu Noguchi (1904-1988), Alberto Carneiro (1937-2017), Louise Nevelson (1899-1988), Lourdes Castro (1930), Germaine Richier (1902-1959), Barnett Newman (1905-1970), Anselm Kiefer (1945), Joseph Beuys (1921-1986), Richard Long (1945), Rui Chafes (1966), Anish Kapoor (1954) and Diogo Pimentão (1973)